Investigation of high performance cathode material for lithium Ion battery (LIB) - Tan, Qi Soon (Nanyang Technological University, 2021)
Over the recent decades, Rechargeable Lithium Ion Batteries (LIBs) have been one of the key research focus that contributes towards technological advancement of electronic devices. Along with rising concerns towards climate change, there have been a shift in focal point for engineering, with accelerating interests towards sustainability and green innovations. One of the solutions towards a sustainable future is through the proliferation of electric vehicles, which relies heavily on electrochemical performance of LIBs. To attain greater driving range, numerous researches have been working on Nickel-rich cathode materials in an effort to improve reversible capacity of LIBs. In this report, optimal synthesis parameters of LiNi0.8Mn0.1Co0.1O2 (NMC811) under atmospheric air have been explored. Transitional metal hydroxide precusor of 8:1:1 ratio will first be prepared via co-precipitation of transition metal sulfate. Using the hydroxide precursor, various temperature and holding time for atmospheric air calcination process have been experimented. Synthesised product will then be characterised via X-ray Diffraction and Scanning Electron Microscope to ensure that single crystalline NMC811 has been synthesised. Sample will then be coated onto Aluminum sheet to be used as cathode active material. Upon coating, the cathode will have its electrochemical performance tested through the use of Gravimetric Charge/Discharge, Electrochemical Impedance Spectroscopy and Cyclic Voltemetry. This reports demonstrates a proof of concept on the feasibility of NMC811 calcination under atmospheric conditions, with relatively stable cycling performance and high efficiency.